The Effect of CSR, Earnings Management, and Financial Performance on Firm Value: Moderated by Audit Committee: Moderated by Audit Committee - Ivana Hemas Nandya Sukoco; Faridhatun Faidah; Hutomo Rusdianto (Universitas Muhammadiyah Purwokerto, 2026)
This study aims to analyse the influence of corporate social responsibility, earnings management, and financial performance on firm value, with the audit committee as a moderating variable, in transportation & logistic companies listed on the Indonesia Stock Exchange for the period 2020-2024. This research is a quantitative, descriptive study using secondary data from companies' financial statements for the period 2020-2024, obtained from the IDX website. The sampling method used was purposive, yielding a sample of 10 companies. The data analysis technique used was moderated regression analysis with SPSS Version 29. The results of the study showed that corporate social responsibility did not have a significant effect on firm value; earnings management did; and financial performance did not. Additionally, the audit committee was unable to moderate the influence of corporate social responsibility, earnings management and financial performances on firm value.